PENGARUH STRUKTUR ASET, KEBIJAKAN DIVIDEN, RISIKO BISNIS, DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANGx - Christine Christine; Nurainun Bangun (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims to examine the effect of assets structure, dividend policy, business risk, and profitability on debt policy in manufacturing companies listed in Indonesia Stock Excange during 2017-2019. Sample was selected using purposive sampling method amounted to 40 companies. Data processing technique using SPSS version 25 and Microsoft Excel 2013. The result of this research shows that profitability has significant effect on debt policy, while assets structure, dividen policy, and business risk have no significant effect on debt policy. The implications of this study is to decide about debt policy that will company use with the factors that influence debt policy.